Microgrid control methods toward achieving sustainable energy management: A bibliometric analysis for future directions - Roslan M.F.; Hannan M.A.; Ker P.J.; Mannan M.; Muttaqi K.M.; Mahlia T.I. (Elsevier Ltd, 2023)
Cost effectiveness; Electric power system control; Energy efficiency; Energy management; Integrated control; Publishing; Sustainable development; Bibliometrics analysis; Control energy; Control methods; Highly cited article; In-control; Microgrid; Microgrid control; Microgrid control method; Scopus database; Sustainable energy management; Energy management systems